Comparative study of serum urea, creatinine and C-reactive protein level in chronic kidney disease patients with healthy subjects - Nirwan, Dileep Singh; Vyas, R. K.; Jain, Sunil (International Journal of Research in Medical Sciences, 2017)
Background: Chronic diseases are a leading cause of morbidity and mortality in India. Globally, chronic kidney disease is the 12th cause of death and the 17th cause of disability, respectively. CKD is defined as kidney damage or glomerular filtration rate (GFR) <60 mL/min/1.73 m2 for 3 months or more, irrespective of cause. The present study aimed to find out correlation between serum urea, creatinine and C-reactive protein (CRP) level among patients suffering from chronic kidney disease in an urban based tertiary care hospital in Bikaner, western Rajasthan, India. Methods: This study was conducted at Sardar Patel Medical College and Associated Hospitals at Bikaner, Rajasthan from August 2015 to December 2016. There were 50 cases and 50 controls in the age groups from 10 to 60 yearrs. We took fresh samples and performed required tests following standard protocol. CRP has been done by Antigen Antibody reaction (latex method). RFT has been performed on semi-automatic analyzer. Results: Levels of serum urea and creatinine were significantly raised in CKD patients (p-value<0.005) and CRP level was raised in 52% cases. While 48% cases having normal level %), which requires further study. Renal function tests were significantly higher in cases than controls. Conclusions: Serum creatinine and urea level were significantly higher in cases as compared to control group.